Impact of Korea-ASEAN FTA on the technology level of Korean manufacturing firms - BAE, Yunjin (KDI School, 2015)
Recently FTA is greatly contributing to enhancement of world trade by bilateral tariff reduction. Korea has made numbers of FTAs with major economies in the world; among them, Korea-ASEAN FTA is of greatest importance to Korea since ASEAN is one of its major trade partners. There have been studies which expected that not only the trade size between the two economies would enlarge but also productivity of Korean manufacturing sector would increase. Yet these studies bear limitations that they are qualitative as well as ex ante. This paper quantitatively measured the impact of tariff reduction by Korea-ASEAN FTA on R&D expenditure and TFP, as proxies for their technology level, of Korean manufacturing firms using the OLS regression analysis; as a result, it appeared that the reduced tariff of ASEAN toward Korea had contributed to Korean manufacturing firms to decrease their R&D spending but to increase their TFP
Thesis(Master) --KDI School:Master of Development Policy,2015